KEADILAN GENDER DALAM HUKUM WARIS: ANALISIS BAGIAN ANAK PEREMPUAN PERSPEKTIF KOMPILASI HUKUM ISLAM - Ahmad Burhanuddin; Ihsan Kurniawan; Begu Halomoan; Dapot Panjaitan (I’tiqadiah: Jurnal Hukum dan Ilmu-ilmu Kesyariahan, 2025)
The issue of gender justice in Islamic inheritance law is often debated, especially regarding the difference in inheritance shares between sons and daughters. This study aims to analyze how the principle of gender justice is applied in the practice of inheritance distribution based on the Compilation of Islamic Law (KHI), particularly with regard to daughters, as well as how the community perceives these provisions. This study uses a qualitative approach with field research in a village that actively applies Islamic inheritance law. Data was collected through in-depth interviews with heirs, religious leaders, and village officials, as well as analysis of inheritance distribution documentation. The results of the study show that although the KHI normatively stipulates that female children receive half the share of male children, its application in society is often distorted due to the influence of patriarchal culture, social pressure, and ignorance of women's rights. In some cases, female children even receive a much larger share based on “voluntariness” or “respect.” This study recommends strengthening gender-based legal awareness and the need to reactualize the values of maqāṣid al-syarī‘ah in the implementation of Islamic inheritance law to make it more fair and contextual.